Some integrals of the products of Laguerre polynomials - Lee, PA; Srivastava, HM; Ong, SH (2001)
The evaluation of an integral of the product of Laguerre polynomials was discussed recently in this Journal by Mavromatis [12] (1990) and Lee [9] (1997) [see also Ong and Lee [14] (2000)]. The main object of the present sequel to these earlier works: is to consider a family of such integrals of the products of Laguerre, Hermite, and other classical orthogonal polynomials in a systematic and unified manner. Relevant connections of some of these integral formulas with various known integrals, as well as the computational and numerical aspects of the results presented here, are also pointed out.